A comprehensive review of nutrient-energy-water-solute recovery by hybrid osmotic membrane bioreactors. Issue 6 (January 2021) - Yang, Yu-Li; Wu, You; Lu, Yu-Xiang; Cai, Yun; He, Zhen; Yang, Xiao-Li; Song, Hai-Liang
Graphical abstract: Highlights: NEWS recovery is the first time raised in the OMBR and its hybrid systems. NEWS recovery includes nutrient-energy-water-solute recovery. NWF, SRR, NRR, and NEP are proposed to in-depth analysis of NEWS recovery. The effects of major operating factors on NEWS recovery are evaluated. Operational strategies should be employed to enhance NEWS recovery. Abstract: Hybrid osmotic membrane bioreactor (OMBR) takes advantage of the cooperation of varying biological or desalination processes and can achieve NEWS (nutrient-energy-water-solute) recovery from wastewater. However, a lack of universal parameters hinders our understanding. Herein, system configurations and new parameters are systematically investigated to help better evaluate recovery performance. High-quality water can be produced in reverse osmosis/membrane distillation-based OMBRs, but high operation cost limits their application. Although bioelectrochemical system (BES)/electrodialysis-based OMBRs can effectively achieve solute recovery, operation parameters should be optimized. Nutrients can be recovered from various wastewater by porous membrane-based OMBRs, but additional processes increase operation cost. Electricity recovery can be achieved in BES-based OMBRs, but energy balances are negative. Although anaerobic OMBRs are energy-efficient, salinity accumulation limits methane productions. Additional efforts must be made to alleviate membrane fouling, control salinity accumulation, optimize recovery efficiency, and reduce operation cost. This review will accelerate hybrid OMBR development for real-world applications.